ANALISIS HARGA SAHAM PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hery Aviantoro (2021)
This research is included in quantitative research with the aim of find out whether there is an effect of profitability, liquidity, and solvency to stock prices. Object selected in this study are property and real estate companies registered in Indonesia Stock Exchange using a sample of 29 companies during period 2017 - 2019. The hypothesis in this study was tested with a level of significance of 5%, using Panel Data Regression Analysis Method with the computer program E-Views 11. The results found from this study are (1) there is no effect between profitability and stock prices, (2) there is no there is an influence between liquidity and stock prices, and (3) there is the effect of solvency on stock prices.